Chivalry and romance in the English Renaissance - Davis, Alex, 1973- (Studies in Renaissance literature (Woodbridge, Suffolk, England) ;, 2003)
Chivalry and Romance in Renaissance England offers a reinterpretation of the place and significance of chivalric culture in the sixteenth and seventeenth-century and explores the implications of this reconfigured interpretation for an understanding of the medieval generally.